Clube de Ciências Digital Interativo - Masson, Rafaela; Barbosa, Ellen Francine (Revista de Graduação USP, 2017)
The Interactive Digital Science Club consisted of extra-class activities that favored the experience of scientific methodology (in the areas of Chemistry, Physics, Mathematics, Computation and Biology) in order to repeat the achievements of scientists in laboratories. In addition, it consisted of bringing the students closer to the university, making them aware of the research fields, laboratories and activities within the university. The Interactive Digital Science Club, for its activities, counted on the use of an internet blog in which the participants recorded the results of the activities carried out. This project had as target audience students of first and second year high school of public education institutions and was developed within the scope of the Instituto de Estudos Avançados (IEA), Polo São Carlos activities.